Aesthetic ideal, poetry and artistic photography in Si deseamos el mar, by Juan Carlos Garyayo and Pierre Morlet (XXI Century. Spanish Literature and Culture, 2024)
Study of the aesthetic and poetic keys of the interartistic book Si deseamos el mar, by two musicians, the Spanish pianist Juan Carlos Garvayo (Motril, 1969) and the French cellist Pierre Morlet (Bourg-la-Reine, 1969), authors, respectively, of the poems and artistic photographs that come into contact, which explains the occasional use of ekphrasis. The photographs in turn maintain an intra-artistic dialogue with the painting. The article analyzes the title and meaning of the symbol of the sea in the collection of poems, and also addresses the nostalgia of life lived and the experience of beauty as an aesthetic ideal to conclude with an approach to the modes of poetic expressiveness.
Keywords: Si deseamos el mar; Juan Carlos Garvayo; Pierre Morlet; Spanish poetry; artistic photography